Research on routing strategy of wireless sensor network in intelligent substation based on improved EEUC algorithm - LIU Yuming; CUI Chen; SUN Yanzhi; LI Xu; TIAN Feng (Diance yu yibiao)
Aiming at the problem of uneven distribution of node energy consumption in wireless sensor network routing strategy in intelligent substation, a non-uniform clustering algorithm based on dynamic clustering radius optimization is proposed for wireless sensor network routing in intelligent substation on the basis of auxiliary equipment monitoring system in intelligent substation. The cluster head nodes are selected from two aspects (residual energy and spatial position) to make their distribution more uniform, and balance the energy consumption of cluster head nodes through dynamic competition radius. The feasibility of the proposed method is verified through comparative analysis of its performance through simulation. The results show that compared with conventional routing algorithms, the proposed method can effectively balance network energy consumption and improve cluster head node energy consumption, average node energy consumption, network lifecycle, and throughput, which has certain application value.